From the Vilna Ghetto to Nuremberg memoir and testimony - Suzkever, Abraham 1913-2010 (A Yiddish Book Center Translation, 2021)
In 1944, Yiddish poet Abraham Sutzkever was airlifted to Moscow from the forest where he had spent the winter among partisan fighters. He was encouraged by Ilya Ehrenburg to write a memoir. From the Vilna Ghetto to Nuremberg returns readers to a moment when the scale of the Holocaust was first coming into focus, through the eyes of one survivor who attempted to make sense of daily life, resistance, and death in the ghetto.